Seasonal wind pattern model development for coral reef monitoring - Deros S.N.M.; Din N.M.; Norzeli S.; Asmat A.; Mansor S. (Mattingley Publishing, 2023)
Conveyors; Reefs; Surface waters; Wind; Coral reef; Ekman transport; Mixed layer; Northeast monsoon; Wind patterns; Atmospheric thermodynamics